Using a Concept Inventory to Assess the Reasoning Component of Citizen-Level Science Literacy: Results from a 17,000-Student Study - Edward B. Nuhfer (Journal of Microbiology & Biology Education, 2015)
After articulating 12 concepts for the reasoning component of citizen-level science literacy and restating these as assessable student learning outcomes (SLOs), we developed a valid and reliable assessment instrument for addressing the outcomes with a brief 25-item science literacy concept inventory (SLCI). In this paper, we report the results that we obtained from assessing the citizen-level science literacy of 17,382 undergraduate students, 149 graduate students, and 181 professors. We address only findings at or above the 99.9% confidence level. We found that general education (GE) science courses do not significantly advance understanding of science as a way of knowing. However, the understanding of science’s way of knowing does increase through academic ranks, indicating that the extended overall academic experience better accounts for increasing such thinking capacity than do science courses alone. Higher mean institutional SLCI scores correlate closely with increased institutional selectivity, as measured by the institutions’ higher mean SAT and ACT scores. Socioeconomic factors of a) first-generation student, b) English as a native language, and c) interest in commitment to a science major are unequally distributed across ethnic groups. These factors proved powerful in accounting for the variations in SLCI scores across ethnicities and genders.